FARMERS AWARENESS ON RESPONSIBLE USE OF PESTICIDES IN CUCURBIT GROWING AREAS OF GUNTUR DISTRICT - A. DEVI VARAPRASAD SAI*, CH. SREENIVASA RAO, D.V. SAIRAM KUMAR, D. RAMESH and CH. TIRUMALA DEVI, (The Journal of Research ANGRAU, 2021)
The study on farmer’s awareness on pesticides use and handling was conducted in cucurbitgrowing areas of Guntur district during the year 2020. A large number of cucurbit farmers (86.7%)were not aware about the registered and recommended pesticides on cucurbits as per the InsecticideAct, 1968, while, only 6.6% were aware about the ban of ‘monocrotophos’ on vegetables. All cucurbitfarmers consulted pesticide dealers as source of recommendations, whereas, few young farmersconsult Agricultural Officers in addition to the dealer. About 56.7% farmer’s measured pesticideapproximately, others used measuring cup while preparing spray fluid and all the farmers used stickfor mixing spray fluid. More than half of the spray men (57.0%) did not use any kind of personalprotection equipment, while, 20.0% wore separate clothes with full-sleeves covering the entire hands,only 17.0% spray men wear gloves, and only 6.7% used face mask. Empty pesticide bottles are reusedfor household purposes by 33.3% of the farmers, and most of the farmers (86%) throw theempty / used pesticide bottles /containers in trash bins or open fields, and none of the farmers wereaware of the proper disposal methods.